2017
DOI: 10.1149/08010.1073ecst
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Particles Electrodeposited on Reticulated Vitreous Carbon for Nitrate Reduction

Abstract: The electrocatalytic activity of silver particles electrodeposited on reticulated vitreous carbon (RVC) was evaluated for nitrate reduction. Different morphologies of silver deposits were obtained by varying the deposition potential, AgNO 3 concentration solution, and deposition time. Silver deposit was not uniform due to the three-dimensional shaped electrode. The more elevated regions on the surface present a more intense deposition. The lowest silver ion concentration of 5 mM associated to the lowest deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…After a 60 min deposition (BCF-60), clusters within the dense 5 mm region were 11.08 μm and were 52.3 μm at the boundary. This pattern of particle grown has been reported in literature with electrodeposition on 3D carbon structures …”
supporting
confidence: 81%
See 1 more Smart Citation
“…After a 60 min deposition (BCF-60), clusters within the dense 5 mm region were 11.08 μm and were 52.3 μm at the boundary. This pattern of particle grown has been reported in literature with electrodeposition on 3D carbon structures …”
supporting
confidence: 81%
“…This pattern of particle grown has been reported in literature with electrodeposition on 3D carbon structures. 41 The iodine capture capacity of the CF and BCFs was evaluated using static iodine loading under saturated conditions. 19,42 The results were compared against a silverexchanged faujasite reference material called IONEX Ag-400 (Ag 0 X from Molecular Products).…”
mentioning
confidence: 99%
“…9 These characteristics allow operations that produce relatively high current per unit of cell volume. 10,11 Some authors have reported the use of 3D electrodes to improve the overall electrochemical performance in which the electrode overpotential is controlled by mass transport phenomena. [11][12][13] However, all of these treatments (known as electrolytic cells) require power consumption and a high cost of the treatment process, especially for dilute sample solutions.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Some authors have reported the use of 3D electrodes to improve the overall electrochemical performance in which the electrode overpotential is controlled by mass transport phenomena. [11][12][13] However, all of these treatments (known as electrolytic cells) require power consumption and a high cost of the treatment process, especially for dilute sample solutions. In addition, dilute solutions of silver ion have low conductivities and side reactions tend to occur, thus reducing the efficiency of this system.…”
Section: Introductionmentioning
confidence: 99%